2003
DOI: 10.1002/ffj.1279
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antifungal activity of essential oils isolated from Hypericum hyssopifolium and Hypericum heterophyllum

Abstract: The composition of the hydrodistilled essential oils obtained from the aerial parts of Hypericum hyssopifolium subsp. elongatum var. elongatum and H. heterophyllum Vent. were analysed by means of GC and GC-MS, and 66 compounds were determined in total. The oils showed remarkable differences in chemical composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
110
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(119 citation statements)
references
References 33 publications
7
110
1
1
Order By: Relevance
“…In recent years, several researchers have reported that mono-terpene or sesquiterpene hydrocarbons and their oxygenated derivatives, which are major components of essential oils, exhibit potential antimicrobial activity (Cakir et al, 2004). These findings strongly support the outcomes of this study as L. lucidum flower oil was also found to contain oxygenated sesquiterpenes and their respective hydrocarbons, confirming its efficacy as natural antimicrobial agent.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, several researchers have reported that mono-terpene or sesquiterpene hydrocarbons and their oxygenated derivatives, which are major components of essential oils, exhibit potential antimicrobial activity (Cakir et al, 2004). These findings strongly support the outcomes of this study as L. lucidum flower oil was also found to contain oxygenated sesquiterpenes and their respective hydrocarbons, confirming its efficacy as natural antimicrobial agent.…”
Section: Discussionsupporting
confidence: 89%
“…This strategy had been observed in Picea abies, Abies grandis, and Pinus resinosa, where their main monoterpenes (pinenes), lowered proportions in infected trees in favor of minor monoterpenes such as sabinene and terpinolene (Klepzig et al 1995;Raffa and Berryman 1982a;Zhao et al 2010). Some tree terpenes (usually the main compounds) have low inhibiting effects (Kusumoto et al 2014) or can even enhance the growth of some fungal pathogens (Bridges 1987;Cakir et al 2004;Davis and Hofstetter 2011), because some pathogenic fungi have developed the ability to survive in the presence of the major compounds of their common hosts, detoxifying them or even exploiting them as carbon sources (Kusumoto et al 2014;Wang et al 2013). One plausible hypothesis accounting for our results is that a strong concentration and proportion increase of minor terpenes in infected cypresses would help to lower the success of S. cardinale infection or slow its growth considerably, thereby allowing the tree to react effectively, at least in resistant varieties.…”
Section: Discussionmentioning
confidence: 96%
“…The role of camphor (Kotan et al 2007;Marei et al 2012;Pragadheesh et al 2013;Ramsewak et al 2003) is ambiguous, being inhibitory for some fungi but not others, suggesting slight fungal toxicity. α-Terpineol, however, is a powerful fungal inhibitor ( Cakir et al 2004;Hammer et al 2003;Kossuth and Barnard 1983;Kotan et al 2007;Kusumoto et al 2014;Zhou et al 2014). Thymyl methyl ether is among the least inhibitive chemical structures of thymol to several fungi (Kumbhar and Dewang 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils are volatile and odorous principles of plant secondary metabolism which have wide applications in food flavoring and preservation industries (Bajpai et al, 2012). In recent years, several researchers have reported that terpenes and their oxygenated derivatives, which are the major components of essential oils, exhibit potential antimicrobial activity (Cakir et al, 2004). These findings strongly support the outcomes of this study since G. biloba leaf essential oil was also found to contain terpenes, terpenoids and their respective hydrocarbons, confirming its efficacy as natural antimicrobial agent.…”
Section: Discussionmentioning
confidence: 99%